2003
DOI: 10.1073/pnas.2334257100
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Flory's isolated-pair hypothesis: Statistical mechanics of helix–coil transitions in polyalanine and the C-peptide from RNase A

Abstract: To evaluate Flory's isolated-pair hypothesis in the context of helical peptides, we explore equilibrium conformations of ␣-helixforming polypeptides as a function of temperature by means of replica exchange molecular dynamics in conjunction with the CHARMM͞GB implicit solvent force field and the weighted histogram analysis method. From these simulations, Zimm-Bragg parameters, s and , of Ac-Ala n -NMe are computed as a function of temperature. The values obtained for s(T) and (T) remain unchanged along the len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
63
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 34 publications
17
63
2
Order By: Relevance
“…Table 1 shows s and ZB along with the average number of helical residues, <n>, and average length of a helical segment, <l ZB >, observed in our simulations at different reduced temperatures, T*. At low temperatures, high values of s (1.80) indicate that the alanine residues on the model peptide have a strong preference to form helix over coil, which is in good agreement with preferences observed in experiment (Marqusee et al 1989;Scholtz et al 1991;Charkabartty et al 1994;Chakrabartty and Baldwin 1995) and in the simulations of Okamoto and Hansmann (1995), Garcia and Sanbonmatsu (2002), and Ohkubo and Brooks III (2003).…”
Section: Intrinsic Helical Propensity Of Alaninesupporting
confidence: 91%
See 1 more Smart Citation
“…Table 1 shows s and ZB along with the average number of helical residues, <n>, and average length of a helical segment, <l ZB >, observed in our simulations at different reduced temperatures, T*. At low temperatures, high values of s (1.80) indicate that the alanine residues on the model peptide have a strong preference to form helix over coil, which is in good agreement with preferences observed in experiment (Marqusee et al 1989;Scholtz et al 1991;Charkabartty et al 1994;Chakrabartty and Baldwin 1995) and in the simulations of Okamoto and Hansmann (1995), Garcia and Sanbonmatsu (2002), and Ohkubo and Brooks III (2003).…”
Section: Intrinsic Helical Propensity Of Alaninesupporting
confidence: 91%
“…They found that the helixcoil transition is moderately cooperative over a broad temperature range. Ohkubo and Brooks III (2003) examined equilibrium helix-coil transitions of Ac-Ala n -NMe (n ‫ס‬ 3-20) as a function of temperature by using REMD with the CHARMm/GB implicit solvent force field. They found that the intrinsic helical propensity of alanine measured by the Zimm-Bragg parameters is independent of the chain length.…”
mentioning
confidence: 99%
“…Discrepancies in both global minima of free energy surfaces and detailed local structures, such as salt bridge formation and helical content, have been observed, indicating that room exists for further improvement of the GB implicit solvent models (see Section II, C for more detailed discussions). Nevertheless, successful applications of implicit solvent models to address more specific problems in protein folding have been reported (Karanicolas and Brooks, 2004;Ohkubo and Brooks, 2003). In addition, recent years have seen quite a few successful applications of various GB implicit solvent models to ab initio structure prediction for a number of miniproteins, such as protein A ( Jang et al, 2003a), villin headpiece ( Jang et al, 2003a;Liu and Beveridge, 2002), Trp-cage (Pitera and Swope, 2003), Trp-zip (Okur et al, 2003;Steinbach, 2004;Yang et al, 2004), bba motifs (Jang et al, 2003b), and the fd Coat transmembrane protein .…”
Section: Protein Folding/unfoldingmentioning
confidence: 99%
“…In addition, the hydroxyl groups of the sugar chains are also arranged outwardly in a regular order on the 110 surfaces of microcrystalline cellulose [25], allowing hydrogen bonds to be formed between these surfaces and the T or S of the PT/S-boxes. Alanine is highly flexible, which increases the flexibility of the polypeptide chain [26,27]. Thus, alanine may act as a hinge that renders semi-flexibility to the otherwise-stiff PT/S-box polypeptide chain.…”
Section: Mutant Design Of Accel12b Linkermentioning
confidence: 99%
“…Hence, we defined the PT-box1, (PT) 2 (PS) 4 P, as one PT/S-box unit and then redesigned the LR of AcCel12B to contain 0, 1, 2 and 3 PT/S-box units (Figure 1). which increases the flexibility of the polypeptide chain [26,27]. Thus, alanine may act as a hinge that renders semi-flexibility to the otherwise-stiff PT/S-box polypeptide chain.…”
Section: Mutant Design Of Accel12b Linkermentioning
confidence: 99%